2010
DOI: 10.5194/acp-10-6569-2010
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Antarctic ozone loss from ground-based total column measurements

Abstract: Abstract. The passive tracer method is used to estimate ozone loss from ground-based measurements in the Antarctic. A sensitivity study shows that the ozone depletion can be estimated within an accuracy of ∼4%. The method is then applied to the ground-based observations from Arrival Heights,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 47 publications
7
51
0
Order By: Relevance
“…The low standard deviations, represented by a blue and gray shaded areas, provide information on the low inter-annual variability in the shape of the maximum depleted ozone profile, as other previous studies have pointed out. These data reassert the low inter-annual variability of the Antarctic ozone loss (Kuttippurath et al, 2010). The general evolution of ozone loss inside of the polar vortex exhibits a phase of a slow ozone decline, followed by a period of quick ozone destruction.…”
Section: Selection Of Layers and Time Windowsupporting
confidence: 74%
See 3 more Smart Citations
“…The low standard deviations, represented by a blue and gray shaded areas, provide information on the low inter-annual variability in the shape of the maximum depleted ozone profile, as other previous studies have pointed out. These data reassert the low inter-annual variability of the Antarctic ozone loss (Kuttippurath et al, 2010). The general evolution of ozone loss inside of the polar vortex exhibits a phase of a slow ozone decline, followed by a period of quick ozone destruction.…”
Section: Selection Of Layers and Time Windowsupporting
confidence: 74%
“…Assuming a linear relationship between ozone loss rate and EESC, Hassler et al (2011) found that a reduction of the ozone loss rate at South Pole station (SPS hereafter) will be detectable in 2017-2021 period. In recent years, estimates of the ozone loss rate based on different satellite instrumentation (Tilmes et al, 2006;Sonkaew et al, 2013), ground-based instrumentation (Kuttippurath et al, 2010(Kuttippurath et al, , 2013 and balloon-borne measurements (Hassler et al, 2011;Hoffmann et al, 2009) for the Antarctic region have been published.…”
Section: C Parrondo Et Al: Antarctic Ozone Variability Inside Thmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Kuttippurath et al (2010), the edge of the vortex varies between −30 and −45 potential vorticity units (PVUs) at 475 K during the August-November period. Figure 4 shows the −30 and −45 PVU boundaries of the vortex at 475 K, using the ECMWF operational analysed potential vorticity (PV) field for several example comparisons.…”
Section: Sounding Balloons/concordiasi Campaign In 2010mentioning
confidence: 99%